Lipidomics as an important key for the identification of beer-spoilage bacteria - Řezanka, T; Matoulková, D; Benada, O; Sigler, K (Letters in applied microbiology, 2015)
Electrospray ionization-tandem mass spectrometry (ESI-MS/MS) was used for characterizing intact plasmalogen phospholipid molecules in beer-spoilage bacteria. Identification of intact plasmalogens was carried out using collision-induced dissociation and the presence of suitable marker molecular species, both qualitative and quantitative, was determined in samples containing the anaerobic bacteria Megasphaera and Pectinatus. Using selected ion monitoring (SIM), this method had a limit of detection at 1 pg for the standard, i.e. 1-(1Z-octadecenyl)-2-oleoyl-sn-glycero-3-phosphoethanolamine and be linear in the range of four orders of magnitude from 2 pg to 20 ng. This technique was applied to intact plasmalogen extracts from the samples of contaminated and uncontaminated beer without derivatization and resulted in the identification of contamination of beer by Megasphaera and Pectinatus bacteria. The limit of detection was about 830 cells of anaerobic bacteria, i.e. bacteria containing natural cyclopropane plasmalogenes (c-p-19:0/15:0), which is the majority plasmalogen located in both Megasphaera and Pectinatus. The SIM ESI-MS method has been shown to be useful for the analysis of low concentration of plasmalogens in all biological samples, which were contaminated with anaerobic bacteria, e.g. juice, not only in beer. Significance and impact of the study: Electrospray ionization-tandem mass spectrometry (ESI-MS/MS) using collision-induced dissociation was used to characterize intact plasmalogen phospholipid molecules in beer-spoilage anaerobic bacteria Megasphaera and Pectinatus. Using selected ion monitoring (SIM), this method has a detection limit of 1 pg for the standard 1-(1Z-octadecenyl)-2-oleoyl-sn-glycero-3-phosphoethanolamine and is linear within four orders of magnitude (2 pg to 20 ng). The limit of detection was about 830 cells of bacteria containing natural cyclopropane plasmalogen (c-p-19:0/15:0). SIM ESI-MS method is useful for analyzing low concentrations of plasmalogens in biological samples contaminated with anaerobic bacteria, e.g. beer or juice.
Keywords: Megasphaera; Food Microbiology; Pectinatus; Limit of Detection; hmotnostní spektrometrie s elektrosprejovou ionizací; potravinářská mikrobiologie; limita detekce; pivo; tandemová hmotnostní spektrometrie; Beer; Spectrometry, Mass, Electrospray Ionization; plasmalogeny; Plasmalogens; Tandem Mass Spectrometry